Alkali and alkaline earth zinc and lead borate glasses: Sintering and crystallization - Lina Heuser; Marianne Nofz; Ralf Müller (Journal of Non-Crystalline Solids: X, 2022)
Glasses in the systems Me2O-ZnO-B2O3 with Me = Li, Na, K, Rb (MeZB), Na2O-ZnO-CuO-B2O3 (NZCuB), CaO-ZnO-B2O3 (CaZB), and Li2O-PbO-B2O3 (LPbB) as a reference, were studied by differential thermal analysis, dilatometry, rotational viscometry, and heating microscopy. A decrease of viscosity and sintering range was found with decreasing number of fourfold coordinated boron. The viscosity of the alkali zinc borate glasses varies only slightly. LPbB and CaZB stand out by their reduced and increased viscosities, respectively. Sodium, potassium, and calcium zinc borate glasses possess a fragility above 76. All glasses were sintered to full density before crystallization. Mostly binary zinc borate phases govern crystallization. A ternary crystalline phase was detected only in the potassium containing sample. The Weinberg glass stability parameter ranges between 0.07 and 0.12. This is caused by the presence of several crystalline phases and varying melting points of even the same crystalline phase in different glass matrices.